Repertórios de ação coletiva e políticas públicas: uma análise a partir da construção da Política de Prevenção ao Suicídio no município de Santa Cruz do Sul (RS). - Stavizki Junior, Carlos (2021)
This master's dissertation analyzes the repertoires of action of subjects involved in the construction of a suicide prevention policy in the county Santa Cruz do Sul/RS. Having as theorical reference the concept of Charles Tilly's Repertoire of Collective Action and the historical analysis regarding political construction surrounding suicide prevention in Brazil, the study highlights opportunities and political threats present in the process of developing a public policy. It also brings a discussion about the phenomenon of suicide in contemporary world, defending a relational approach between the material conditions of life and sociability in the context of neoliberalism and the increase of self-provoked deaths in the territory observed by this study. The research that empirically supports this discussion is based on four guiding questions. The first one, questions how the changes in the political conjuncture of the territory have impacted/reverberate in the construction of suicide prevention policies. The second aims at understanding the political importance of the Santa Cruz do Sul Municipal Committee on Suicide Prevention and its subjects in the current context of social movements focused on building a political agenda around the issue of suicide. The third refers to the trajectory of this Municipal Committee until its constitution, seeking to identify the repertoires perceived in the collective action of the subjects that compose this place. Finally, the fourth evaluates how the opportunities and political threats define/redefine the subjects forms of action involved in the construction of a municipal suicide prevention policy. Both the research questions and the theoretical arguments of the dissertation are based on the materialistic-historical method, congregating the scientific criteria of work to a critical position on the investigated phenomena. Thus, it is revealed that the subjects' repertories of action have a historical connection with the repertories used by the Antimanicomial Struggle movements and the Psychiatric Reform in Brazil. In addition, it is revealed that the political arrangements that manage the State, in its different instances, influence the choice of repertories of action, as well as highlight threats and political opportunities for building public policies. Finally, it unveiled that the search for institutionality and the involvement of civil society in suicide prevention campaigns in the territory are innovative repertories in the context of the 21st century, even if its effectiveness in implementing public policies has not been confirmed.